Effect of catastrophic disaster in financial market contagion - Md. Noman Siddikee; Mohammad Mafizur Rahman (Cogent Economics & Finance, 2017)
The study examined the contagion effect of financial market volatility from Australian capital market to Indian, New Zealand, Hong Kong, Chinese, Taiwan, and Japanese capital markets due to Australian catastrophe. In the first stage, we employed two-variable vector autoregression (VAR) model for calculating the residuals of the daily index return. In the second stage, we used adjusted correlation coefficient for detecting the significant increase in correlation coefficient of the VAR residuals after the catastrophes. Finally, Fishers r to z transformation was used for identifying contagion. After Victoria bushfire, a significant increase in the adjusted correlation coefficient of Australia with India and Hong Kong and their respective z > +1.96 validates contagion. The adjusted correlation coefficient of Australia with China and Japan increased after the Victoria bushfire but the z < +1.96 with (p > 0.05) does not confirm contagion, but rather exposed the persistence of high economic linkage. Apart from this, a significant decrease in the correlation coefficients with New Zealand is evident with corresponding z < −1.96 and (p < 0.05) advocates low economic linkage among them. After New South Wales (NSW) bushfire, contagion persists only between Australia and Hong Kong and the economic linkage of Australia and Taiwan has notably increased. The negative z score with (p > 0.05) confirms absence of contagion effect in New Zealand, India, and Japan after shocks. The findings of the study recommend the Hong Kong and Indian investors to carefully examine the catastrophe-sensitive industry before taking major investment decisions.
Keywords: C01; E44; G15; 330; financial market volatility; contagion; environmental catastrophe